Prehospital ketamine administration to pediatric trauma patients with head injuries in combat theaters - Hill, Guyon J.; April, Michael D.; Maddry, Joseph K.; Schauer, Steven G. (The American journal of emergency medicine, 2019)
Head injuries frequently occur in combat. Tactical Combat Casualty Care (TCCC) guidelines recommend pre-hospital use of ketamine for analgesia. Yet the use of this medication in patients with head injuries remains controversial, particularly among pediatric patients. We compare survival to hospital discharge rates among pediatric head injury subjects who received prehospital ketamine versus those who did not. We queried the Department of Defense Trauma Registry (DODTR) for all pediatric (<18 years of age) subjects from January 2007 to January 2016. We performed a sub-analysis of subjects with an abbreviated injury severity score for the head of 3 (serious) or higher and at least one documented Glasgow Coma Score (GCS) ≤13. Of the 3439 pediatric patients within our dataset, 555 subjects met inclusion criteria for head injury – 36 (6.5%) received prehospital ketamine versus 519 (93.5%) who did not. There was no significant difference noted between groups regarding median age (10 versus 8, p = 0.259), percent male gender (72.2% versus 76.3%, p = 0.579), mechanism of injury (p = 0.143), median composite injury scores (22 versus 20, p = 0.082), median ventilator-free days (28 versus 27, p = 0.068), median ICU-free days (27.5 versus 27, p = 0.767), median hospital days (3.5 versus 4, p = 0.876) or survival to discharge (66.7% versus 70.7%, p = 0.607). Within this data set, we were unable to detect any differences in mortality among pediatric head trauma subjects administered ketamine compared to subjects not receiving this medication in the prehospital setting.